If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + -32 + -35 = 5 Reorder the terms: -32 + -35 + 6p = 5 Combine like terms: -32 + -35 = -67 -67 + 6p = 5 Solving -67 + 6p = 5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '67' to each side of the equation. -67 + 67 + 6p = 5 + 67 Combine like terms: -67 + 67 = 0 0 + 6p = 5 + 67 6p = 5 + 67 Combine like terms: 5 + 67 = 72 6p = 72 Divide each side by '6'. p = 12 Simplifying p = 12
| x+5=56 | | 3x^2+14x+31=0 | | x-2/2x^2-9x+10=0 | | -4x^2-11x-6=0 | | 1/2(c+8)=1/4c | | 2x-24=6x | | 8x+82=3x+2 | | 6ln(x^2-3)-7=12.2 | | 7+18r-3=6r+64-3r | | -12x-114=5x+11+8x | | -x^2-x+2=3x^2+10x+8 | | 8(y-3)=3y-59 | | 6(m-1/9)=55/12 | | x-4y=-25 | | 18-c+36=49 | | x+(x+35)+(2x-39)=592 | | 2(4d-6)=5d+12 | | x+13+1=44 | | 4k+4=2(k+5) | | 2/3x+1/9y=-19/27 | | 2.5x+10=1.5+17 | | 2r+4r=12 | | x+(x+100000)=600000000 | | 4y-19-y=-59+y | | -6-8(x+7)=-32-2x | | z/8=-6 | | -7x+26=6x | | 2x^3-19=12x | | x+13=44 | | (x^3+5x-18)/(x-2) | | W+15-28+5=177 | | -47-2x=7x+21 |